2008
DOI: 10.1159/000121075
|View full text |Cite
|
Sign up to set email alerts
|

Plant sex chromosomes: molecular structure and function

Abstract: Recent molecular and genomic studies carried out in a number of model dioecious plant species, including Asparagus officinalis, Carica papaya, Silene latifolia, Rumex acetosa and Marchantia polymorpha, have shed light on the molecular structure of both homomorphic and heteromorphic sex chromosomes, and also on the gene functions they have maintained since their evolution from a pair of autosomes. The molecular structure of sex chromosomes in species from different plant families represents the evolutionary pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 198 publications
1
39
0
Order By: Relevance
“…Moreover, recent findings in Drosophila suggest that the Y chromosome has an important role in male fitness and also contributes to adaptive phenotypic variation through a regulatory role of Y-linked polymorphic elements in gene expression (Lemos et al, 2008). In contrast, a gradual degeneration appears to be the primary driving force in evolutionarily young Y chromosomes as shown in the plant models Carica papaya and Silene latifolia (Jamilena et al, 2008). In addition, once the degenerated Y chromosome fuses or translocates to an autosome, a new cycle of its evolution starts.…”
Section: Evolution Of Neo-sex Chromosomes In Samia Cynthiamentioning
confidence: 99%
“…Moreover, recent findings in Drosophila suggest that the Y chromosome has an important role in male fitness and also contributes to adaptive phenotypic variation through a regulatory role of Y-linked polymorphic elements in gene expression (Lemos et al, 2008). In contrast, a gradual degeneration appears to be the primary driving force in evolutionarily young Y chromosomes as shown in the plant models Carica papaya and Silene latifolia (Jamilena et al, 2008). In addition, once the degenerated Y chromosome fuses or translocates to an autosome, a new cycle of its evolution starts.…”
Section: Evolution Of Neo-sex Chromosomes In Samia Cynthiamentioning
confidence: 99%
“…However, plant sex chromosomes have been found from moss to flowering plants, including familiar crop species, such as asparagus, hop, kiwi fruit, papaya and spinach (Matsunaga and Kawano, 2001). The ancient Y chromosome in the liverwort Marchantia polymorpha is small and largely heterochromatic (Yamato et al, 2007), whereas most Y chromosomes in flowering plants are the largest chromosomes in male genomes and many plant sex chromosomes are morphologically indistinguishable (Matsunaga, 2006;Jamilena et al, 2008). Why do sex chromosomes in flowering plants seem to retain their primitive characteristics similar to a pair of autosomes?…”
mentioning
confidence: 99%
“…The large size Y-chromosome indicated the possibility of accumulation of repeated sequences, which is a sign of evolution of plant Y-chromosomes (Jamilena et al 2008, Bergero et al 2008, Heslop-Harrison and Schwarzacher 2011, Mariotti et al 2009). Moreover, Sousa et al (2013) reported that the subterminal repetitive sequences may have accumulated on the Y-chromosomes.…”
Section: Nature Of Y-chromosomementioning
confidence: 99%